Empirical and Numerical Evaluation of Mechanisms in Gas Production from CH4-Hydrates: Emphasis on Kinetics, Electrical Resistivity, Depressurization and CO2-CH4 Exchange - Birkedal, Knut Arne (Energy & Fuels, 2013)
Focus is shifted towards renewable energy and sources of natural gas as the demand for cleaner energy continues to increase with global awareness on anthropogenic climate change. Methane (CH4) provides advantages such as high enthalpy upon combustion and low carbon imprint compared to other fossil fuels. Natural gas is therefore predicted to play an important role as the world moves from coal dependency towards a cleaner and more sustainable energy future. Natural gas hydrate is a solid state of gas and water, where water molecules interconnect through hydrogen bonding to form a cavity which is stabilized by a gas molecule through van der Waals interaction forces. This reaction occurs where water and CH4 coexist at low temperature and high pressure. In nature, such conditions are typically found in permafrost and sub-marine environments. Vast energy resources are associated with gas hydrates, where different models suggest that hydrates contain 1015 to 1017 m3 CH4 at standard temperature and pressure (STP). In comparison, the annual gas consumption in the US is about 7•1011 m3. Gas hydrates may therefore become a significant contributor in the future energy mix. Current technological challenges are related to in situ characterization for accurate saturation estimates, further advances in production technologies and continuous improvements of available numerical models through comparison with actual fieldand core-scale data. A synergy between gas production and safe CO2 storage is achieved through CO2 sequestration in hydrate bearing sediments, where CO2 replaces the existing CH4 molecule within the hydrate crystal. The process occurs because CO2 offers favorable thermodynamic conditions. Salt was observed to impact the hydrate formation rate and the amount of excess water in Paper 1. Depressurization and diffusion-driven CO2 exchange were compared, where Magnetic Resonance Imaging (MRI) was used to monitor production in situ. CO2-CH4 exchange was more abundant for high residual brine, and therefore sensitive to ...